A quantitative model of the distribution of Mute Swans wintering in Danish waters - Petersen, Bjørn Molt (Wildfowl, 2000)
The winter distribution of Mute Swans (Cygnus olor) in Danish waters was analysed in terms of habitat characteristics. Mute Swan densities obtained from four countrywide aerial surveys were investigated: the habitat variables considered were water depth, ratio of coastline to counting unit area, sediment types and concentrations of nutrients. Using a linear regression procedure, a model resulted that explained c. 44% of the density variation. As a next step, systematic variation in density depending on geographical position was added. This resulted in an increase in explanatory power to c. 66% of the variation. The resulting model of the spatial distribution of Mute Swans wintering in Denmark conforms well with reality, and demonstrates that there is a strong relationship between habitat variables and densities. Furthermore, the model predicts that unexploited habitat is available for the species in northwestern Denmark. Distributions and densities for two years with a total of c. 45,000 wintering swans were compared with another two years when numbers increased to c. 73,000. This increase did not result in an increased exploitation of the northwestern areas, identified as being partly unutilised by the model, neither did it result in a spread over larger areas. It is therefore suggested that either the carrying capacity for wintering swans in Denmark was not reached in any of the four census periods, not even in the southeastern areas with the highest densities or that a behavioural or energetic barrier prevents the utilisation of the northwestern part of Denmark by Mute Swans.